Challenges facing female leaders in public general education schools in the Republic of Yemen: an analytical study - Alshameri, Eman Ahmed Mohammed Abdulatef; Chusnan M. Ag, Masyitoh; Bahri, Saiful (ScienceRise: Pedagogical Education, 2026)
This study aimed to identify, from the perspectives of the female principals and vice-principals themselves, the difficulties they face in public general education schools within the Capital Secretariat of Sana'a. The research problem emanated from the researchers’ own observations pertaining to the challenges impacting the female leaders in executing their leadership roles. In addition, there is an absence of research in the context of Yemen. The authors utilized the descriptive analytical method and constructed a questionnaire, founded on pertinent educational literature and previous studies. The sample comprised 236 female principal and vice principal of public education schools in the districts of Ma'een and As-Saba'in of the Capital Secretariat, Sana'a. In the analysis of data, the authors relied on the measure of central tendency (arithmetic mean) and the measure of dispersion (standard deviation). The mean for the challenges faced by female leaders was 3.14, thus, the challenges were moderate. The authors also highlight the female leaders' high self-confidence. This is evident in the statement “I possess the necessary competence to overcome leadership challenges in the work environment” as this statement was ranked first. On the contrary The authors state that the challenges were mainly attributed to unavailability of financial resources, minimal backing from the supervisory bodies and absence of the institutions' concern about female leaders